1993
DOI: 10.1007/bf01474682
|View full text |Cite
|
Sign up to set email alerts
|

Transport ofl-lactate by cultured rat brain astrocytes

Abstract: Several reports indicate that lactate can serve as an energy substrate for the brain. The rate of oxidation of this substrate by cultured rat brain astrocytes was 3-fold higher than the rate with glucose, suggesting that lactate can serve as an energy source for these cells. Since transport into the astrocytes may play an important role in regulating nutrient use by individuals types of brain cells, we investigated the uptake of L-[U-14C]lactate by primary cultures of rat brain astrocytes. Measurement of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
82
3
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 33 publications
7
82
3
1
Order By: Relevance
“…Additionally, cultured neurons, astrocytes, and oligodendrocytes have the capacity to transport and utilize lactate, pyruvate, and ketone bodies (8,32,38). These studies have also indicated that lactate transport is saturable, proton dependent, and inhibited by cinnamates (1,7,22,34), all of which are characteristics of the MCT (reviewed in Ref. 27).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, cultured neurons, astrocytes, and oligodendrocytes have the capacity to transport and utilize lactate, pyruvate, and ketone bodies (8,32,38). These studies have also indicated that lactate transport is saturable, proton dependent, and inhibited by cinnamates (1,7,22,34), all of which are characteristics of the MCT (reviewed in Ref. 27).…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies, carrier-mediated uptake of lactate into astrocytes was blocked by millimolar concentrations of 4-CIN (Tildon et al, 1993;Broer et al, 1997). Application of 4-CIN (5 mM) reversibly inhibited the LIA in cortical astrocytes (Fig.…”
mentioning
confidence: 90%
“…Astrocytes have been found to express predominantly MCT1, while neurons appeared to express principally MCT2 (Broer et al, 1997). The ability of various transport inhibitors to nearly abolish lactate influx into astrocytes (Tildon et al, 1993;Broer et al, 1997) indicates that the passive influx of lactic acid across the lipid bilayer plays a small role. This is likely to be the case in the present study as well, given the large inhibition of the LIA by 4-CIN; however, a small nonfacilitated component of lactate entry cannot be ruled out.…”
mentioning
confidence: 99%
“…In other studies, no high-affinity uptake was observed (Dringen et al, 1995). In the case of astrocytes, the wide range of K m (7 to > 15 mmol/L) and V max (174 to 250 nmol/min per mg) values that have been observed can probably be attributed to the relative extents to which MCT1 and MCT4 are expressed in the particular culture (Broer et al, 1997;Manning Fox et al, 2000;Tildon et al, 1993). …”
mentioning
confidence: 99%